C(sp(3))-F, C(sp(2))-F and C(sp(3))-H bond activation at silicon(II) centers - Swamy, V. S. V. S. N.; Parvin, Nasrina; Raj, K. Vipin; Sen, Sakya S. (Chemical Communication, 2017)
Silylene [PhC(NtBu)(2)SiN(SiMe3)(2)] (1) cleaves the C(sp(3))-H and C-F bonds of acetophenone and 1,1,1-trifluoroacetophenone, respectively, under mild conditions. The reaction is initiated via a nucleophilic attack from the oxygen to the silicon atom followed by C-F/H bond cleavage. The scope of C-F bond activation has further been extended with C6F6 and C6F5CF3.
Keywords: Boron triple bond; C-F Bond; Fluorinated Building-Block; H Activation; Ketones; N-heterocyclic carbenes; Oxodative Addition; Perfluorinated Arenes; Selective Activation; Transition-Metal Centers

Water mediated deactivation of Co3O4 naonrods catalyst for CO oxidation and resumption of activity at and above 373 K: electronic structural aspects by NAPPES - Jain, Ruchi; Reddy, Kasala Prabhakar; Ghosalya, Manoj Kumar; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2017)
The catalytic activity of the Co3O4 nanorods (NRs) for the CO oxidation reaction and the effect of water on the catalytic reaction have been explored with near-ambient pressure photoelectron spectroscopy (NAPPES) and mass spectral analysis. Comparative NAPPES studies have been employed to understand the elucidation of the catalytic reaction pathway and the evolution of various surface species. The results confirm the suppression of the CO oxidation activity on the Co3O4 NRs in the presence of water vapor. Various type of surface species, such as CO(ads), hydroxyl, carbonate, formate, are found to be present on the catalyst surface depending on the reaction conditions. Vibrational features of CO, O-2, and CO, were observed and shift in binding energy of these features under the reaction conditions directly suggests a change in work function of the catalyst surface. Under dry conditions, CO couples with labile 0 atoms to form CO2; however, under wet conditions, CO predominantly interacts with surface OH groups resulting in the formation of carbonate and formate intermediates. In situ studies of oxidation of CO on Co3O4 shows that CO oxidation depends not only on surface Co3+ concentration but also influenced by Co-3/Co' ratio on the catalyst surface. The carbonate was found to be a reaction inhibitor at room temperature; however, it acts as an active intermediate at 375 K and above. Above the boiling point of water, Co3O4 NR surfaces begin to show the oxidation activity even in the presence of water vapor. The intrinsic role of intermediate species was used to derive a possible reaction mechanism under different reaction conditions.
Keywords: Ambinent-temprature; carbon monoxide; Gas Shift; H Activation; In-situ; Low-temprature oxidation; Molecular-beam; Performance enhancement; Ray Photoelectron-Spectroscopyu; Thin-films

Nickel-catalyzed regioselective C―H alkynylation of pyridones and isoquinolinones using alkynyl bromides - Verma, Suryadev K.; Patil, Harshal R.; Punji, Benudhar (ChemCatChem, 2025)
A straightforward and efficient protocol for the regioselective C & horbar;H alkynylation of 2-pyridones and isoquinolinones with bromoalkynes under nickel catalysis is described. The alkynylation reaction is enabled by a simple and inexpensive Ni(OTf)2/tBubpy catalyst system and uses easily accessible bromoalkynes. The protocol demonstrates a broad substrate scope with up to 95% yield (42 examples) and accommodates synthetically valuable functionalities, such as halides, trifluoromethyl, nitrile, ether, thioether, alkyl silanes, and alkene, as well as heteroarene moieties like pyridinyl, furanyl, and thiophenyl. The pyridinyl directing group on alkynylated 2-pyridones can be smoothly removed to give C6-alkynylated free NH-pyridone. Preliminary mechanistic studies suggest that the alkynylation proceeds via a 2e- oxidative addition pathway involving crucial C & horbar;H activation.
Keywords: alkynylation; C & horbar; H Activation; Mechanism; Nickel; pyridones